Recent Advances in Metal-TADF Emitters and Their Application in Organic Light-Emitting Diodes - To, Wai-Pong; Cheng, Gang; Tong, Glenna So Ming; Zhou, Dongling; Che, Chi-Ming (Frontiers in Chemistry, 2020)
In this contribution, recent advances in new classes of efficient metal-TADF complexes, especially those of Au(I), Au(III) and W(VI), and their application in OLEDs are reviewed. The high performance (EQE = 25%) and long device operational lifetime (LT95 = 5280 hours) achieved in an OLED with tetradentate Au(III) TADF emitter reflect the competitiveness of this class of emitters for use in OLEDs with practical interest. The high EQE of 15.6% achieved in solution-processed OLED with W(VI) TADF emitter represents an alternative direction toward low-cost light-emitting materials. Finally, the design strategy of metal-TADF emitters and their next-stage development are discussed.